Efeitos do disseleneto de difenila em carpas expostas a uma formulação comercial contendo cipermetrina e clorpirifós - Rodrigues, Cíntia Corte Real (2016)
Agricultural activity is one of the main factors that lead to the increase of contaminants in aquatic ecosystems and may cause oxidative stress in fish. The objective of this work was to verify the protective effects of diet supplemented with 3.0 mg/kg of diphenyl diselenide (PhSe)2 in fish exposed to Colosso®, a commercial formulation containing 15% of cypermethrin and 25% of chlorpyrifos. Thirty-two carps were divided into four groups: (1) control, (2) (PhSe)2, (3) Colosso®, (4) Colosso® + (PhSe)2. The fish were exposed during 60 days. The levels of lipid peroxidation in liver were higher in fish exposed to the commercial formulation. However, the fish fed selenium had levels reduced of lipid peroxidation in the same tissue. In gills not occur change in levels of thiobarbituric acid reactive substances (TBARS), but fish fed selenium protein carbonyl levels had less than or similar to the control. The diet containing selenium prevented the formation of protein carbonyls in the group exposed to the commercial formulation. In liver catalase (CAT) activity decreases in all groups compared to control. On the other hand, SOD activity increased in the group exposed to the pesticide, returning to the values of the control when the fish were exposed to Colosso® + (PhSe)2. The activity of the enzyme glutathione peroxidase (GPx) in liver and gill was greater in fish fed with (PhSe)2 supplemented diet. The set of results suggest that selenium presented protective action against the oxidative damage caused by exposure to the pesticide. Its action was important, increasing the activity of GPx, since the same is part of the structural formation of this enzyme.